Implementasi Pencegahan COVID-19 di Perguruan Tinggi: Studi Kasus di Sebuah Perguruan Tinggi Negeri di Kota Kendari - Freddrika Putri; Hanifa Maher Denny; Yuliani Setyaningsih (FORIKES, 2022)
The development of the COVID-19 case phenomenon affects the education sector, especially the Halu Oleo University campus environment. Learning methods that were previously carried out offline or face-to-face are now carried out by a distance learning process. In addition, the campus also applies